Galiellalactone inhibits the STAT3/AR signaling axis and suppresses Enzalutamide-resistant Prostate Cancer. Issue 1 (December 2018) - Thaper, Daksh; Vahid, Sepideh; Kaur, Ramandeep; Kumar, Sahil; Nouruzi, Shaghayegh; Bishop, Jennifer; Johansson, Martin; Zoubeidi, Amina
Abstract Most prostate cancer patients will progress to a castration-resistant state (CRPC) after androgen ablation therapy and despite the development of new potent anti-androgens, like enzalutamide (ENZ), which prolong survival in CRPC, ENZ-resistance (ENZR ) rapidly occurs. Re-activation of the androgen receptor (AR) is a major mechanism of resistance. Interrogating ourin vivo derived ENZR model, we discovered that transcription factor STAT3 not only displayed increased nuclear localization but also bound to and facilitated AR activity. We observed increased STAT3 S727 phosphorylation in ENZR cells, which has been previously reported to facilitate AR binding. Strikingly, ENZR cells were more sensitive to inhibition with STAT3 DNA-binding inhibitor galiellalactone (GPA500) compared to CRPC cells. Treatment with GPA500 suppressed AR activity and significantly reduced expression of Cyclin D1, thus reducing cell cycle progression into S phase and hindering cell proliferation.In vivo, GPA500 reduced tumor volume and serum PSA in ENZR xenografts. Lastly, the combination of ENZ and GPA500 was additive in the inhibition of AR activity and proliferation in LNCaP and CRPC cells, providing rationale for combination therapy. Overall, these results suggest that STAT3 inhibition is a rational therapeutic approach for ENZR prostate cancer, and could be valuable in CRPC in combination with ENZ.